Microwave-Promoted Synthesis of 4-Arylpyrimidines by Pd-Catalysed Suzuki-Miyaura Coupling of 4-Pyrimidyl Tosylates in Water - Caroli-Rezende, M; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Rodríguez-Aguilar, J (Georg Thieme Verlag, 2017)
The Suzuki-Miyaura coupling reaction of 4-pyrimidyl tosylates was investigated with aryl, heteroaryl and alkyl boronic acids. The reaction provided 4-substituted pyrimidines in good-to-excellent yields after one-hour microwave irradiation in water at 100 °C. The method constitutes a fast option for the synthesis of these heterocyclic systems. Copyright © 2017 Georg Thieme Verlag Stuttgart · New York.